1995
DOI: 10.1016/0092-8674(95)90471-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase complexed with dystrophin and absent from skeletal muscle sarcolemma in Duchenne muscular dystrophy

Abstract: Nitric oxide (NO) is synthesized in skeletal muscle by neuronal-type NO synthase (nNOS), which is localized to sarcolemma of fast-twitch fibers. Synthesis of NO in active muscle opposes contractile force. We show that nNOS partitions with skeletal muscle membranes owing to association of nNOS with dystrophin, the protein mutated in Duchenne muscular dystrophy (DMD). The dystrophin complex interacts with an N-terminal domain of nNOS that contains a GLGF motif. mdx mice and humans with DMD evince a selective los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
776
2
15

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 903 publications
(811 citation statements)
references
References 52 publications
18
776
2
15
Order By: Relevance
“…It has been shown that NO inhibits energy-generating pathways and decreases ATP levels in synaptosomes [17]. It is noteworthy that mistargeting of NO synthase from the sarcolemma to the cytoskeleton may be involved in pathological states such as muscle dystrophy [18]. In such conditions, NO may exert inhibition of key enzymes at unwanted sites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that NO inhibits energy-generating pathways and decreases ATP levels in synaptosomes [17]. It is noteworthy that mistargeting of NO synthase from the sarcolemma to the cytoskeleton may be involved in pathological states such as muscle dystrophy [18]. In such conditions, NO may exert inhibition of key enzymes at unwanted sites.…”
Section: Discussionmentioning
confidence: 99%
“…NO has shown to regulate cytoskeletal proteins,116 and nNOS isoform, strongly expressed in glycolytic muscle fibres,117 has been reported as the prime source of NO release from skeletal muscle 118. The importance of NO signalling in muscle physiology is highlighted in mdx mice119 and humans with Duchenne muscular dystrophy 112, 120. NO responses are largely mediated via cysteine (Cys) S ‐nitrosylation or by coordinated interactions with heme or non‐heme Fe and Cu 121…”
Section: Chemistry Of Reactive Oxygen and Nitrogen Species Produced Bmentioning
confidence: 99%
“…Skeletal muscles express two alternatively spliced nNOS isoforms, nNOSμ and nNOSβ, both of which are expressed in fast and slow muscle types (Silvagno et al 1996;Stamler and Meissner 2001;Percival et al 2010, Figure 1). nNOSμ is scaffolded to the subsarcolemmal dystrophin glycoprotein complex (DGC) and neuromuscular junction (Brenman et al 1995(Brenman et al , 1996Adams et al 2000). The sarcolemmal nNOSμ association requires α-syntrophin, dystrophin, and α-dystrobrevin (Brenman et al 1995(Brenman et al , 1996Grady et al 2000;Adams et al 2000Adams et al , 2008.…”
Section: Introductionmentioning
confidence: 99%